An Investigation into Intrinsic and Extrinsic Function in Vagrant Harmonies. (29th April 2022) - NEWTON, NEIL
ABSTRACT: In this article I argue that vagrant harmonies have the ability to imply contexts outside of their current tonal region, which is supplied by their immediate musical surroundings. Viewing vagrants in this way enables their functionality to be compared to that of the magnetosome in saltwater bacteria. To explore harmonic function in relation to biological function, I use Larry Wright's (1973) definition of function and apply it to musical phenomena. This leads to a twofold view of harmonic function in vagrants, where it is both intrinsic and extrinsic. These concepts are then used in extracts of tonal pieces. Finally, I examine the second of Alban Berg's Four Songs, Op. 2, to show how harmonic progressions, when used in this way, can provide an exit from tonality while retaining function.